Nucleotide sequence of the essential region of bacteriophage P4. - Lin, C S (1984)
Nucleotide sequence of one-third of the genome of coliphage P4 has been obtained and mutations virl, epsilon am104, cI405, sidl, and delta 35 identified. The epsilon gene likely encodes a 10 kd protein with epsilon am104 being located at the beginning of the gene. cI405, a proposed repressor gene mutation, is located in a sequence capable of coding for a 15 kd protein. A new class of P4 mutations, ash, is located in the neighborhood of cI405. Two TATA-like sequences are mapped 5' to this cI (ash) sequence. Virl is possibly a promoter-up mutation and is located near or within the replication origin, which is about 400 bp long and AT rich. A sidl mutation is amber that shortens the sid protein by 9 amino acids. The delta gene may encode a 17 kd protein and appears to be coupled with the sid gene translationally. In the 5' side of the sid gene a sequence of CACAAT is the best TATA-like sequence. Sequences of two possible genes that are previously unrecognized and part of the alpha and psu genes are also identified.